2020
DOI: 10.1007/s13659-020-00230-8
|View full text |Cite
|
Sign up to set email alerts
|

UFLC-PDA-MS/MS Profiling of Seven Uncaria Species Integrated with Melatonin/5-Hydroxytryptamine Receptors Agonistic Assay

Abstract: Uncariae Ramulus Cum Uncis (Gou-Teng), the dried hook-bearing stems of several Uncaria plants (Rubiaceae), is a wellknown herbal medicine in China. The clinical application of Gou-Teng is bewildered for the morphological and chemical similarity between different species. In order to discern their chemical and biological difference, an ultra-fast liquid chromatography equipped with ion trap time-of-flight mass spectrometry (UFLC-IT/TOF-MS) combining with melatonin (MT 1 and MT 2 ) and 5-hydroxytryptamine (5-HT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…They further identified that two UR flavanols, catechin and epicatechin had agonistic activity on melatonin receptors. In addition, Zhang et al reported that the extracts of different UR species also displayed agonistic effects on melatonin receptors [ 99 ]. Several new alkaloids isolated from UR show agonistic activities on both MT1 and MT2 melatonin receptors [ 100 , 101 ].…”
Section: The Effects Of Ur Components On 5-ht and Melatonin Signalingmentioning
confidence: 99%
“…They further identified that two UR flavanols, catechin and epicatechin had agonistic activity on melatonin receptors. In addition, Zhang et al reported that the extracts of different UR species also displayed agonistic effects on melatonin receptors [ 99 ]. Several new alkaloids isolated from UR show agonistic activities on both MT1 and MT2 melatonin receptors [ 100 , 101 ].…”
Section: The Effects Of Ur Components On 5-ht and Melatonin Signalingmentioning
confidence: 99%